(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this study, a new approach to a UV-blocking treatment for cotton fabrics was developed by dyeing and finishing in one bath and two steps. In this approach, nano-TiO_2 was used as inorganic anti-ultraviolet agent, adhesives poly (vinyl pyrrolidone) PVP was used to improve the wet fastness. Ultraviolet Spectrometer was used for testing and analysis the anti-ultraviolet ability of the cotton fabric before and after the nano-TiO_2 finishing. The effect of the anti-ultraviolet performance and wet fastness of cotton fabrics with different content of nano-TiO_2 or adhesives were investigated. The results show that the nano-TiO_2 UV finishing can effectively improve the UV blocking ability of cotton fabric. With the increase usage of nano-TiO_2, the UV blocking ability of the treated cotton fabrics was increasing. Wet fastness was decreasing when there was no PVP adhesive while it was increasing when there was PVP adhesive and the ability of UV blocking was also increasing. But the content should be controlled in a moderate range; the ability of UV blocking would decrease if the content was exceeding the appropriate range. The electronic fabric strong-tensile machine was used for testing the tearing and breaking tenacity of the treated fabric and the computer-permeability tester was used for testing its air permeability. The results show that the treatment of nano-TiO_2 in this approach for UV-blocking treatment had little effect on the wear ability of the cotton fabric.